Research capacity-building in teacher education. (2nd January 2021) - Oancea, Alis; Fancourt, Nigel; Robson, James; Thompson, Ian; Childs, Ann; Nuseibeh, Nuzha
ABSTRACT: This paper reviews recent policy understandings of research capacity in teacher education in the UK. It then draws on a case study from Wales to suggest a conceptualisation of research capacity-building in teacher education that encompasses individual, organisational and systemic levels while remaining sensitive to the particulars of professional practice in teacher education. We argue that a healthy ecology of research-rich teacher education practice and policy includes teacher educators based in universities, schools, colleges or other settings, teachers and other education practitioners, students, school management, governors, local authorities, policy makers, research funders, publishers. We recommend a principled approach to public investment in capacity-building initiatives that embraces a vision of collaborative research-rich professional practice and professional development along all career stages, and commits to sustaining more expansive understandings of research culture in organisations, matched by appropriate recognition mechanisms.